1982
DOI: 10.1126/science.7123230
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Imitation of Facial Expression by Neonates

Abstract: Human neonates (average age, 36 hours) discriminated three facial expressions (happy, sad, and surprised) posed by a live model as evidenced by diminished visual fixation on each face over trials and renewed fixations to the presentation of a different face. The expressions posed by the model, unseeen by the observer, were guessed at greater than chance accuracy simply by observing the face of the neonate, whose facial movements in the brow, eyes, and mouth regions provided evidence for imitation of the facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
141
0
6

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(161 citation statements)
references
References 13 publications
6
141
0
6
Order By: Relevance
“…There is evidence that such automatic mimicry is innate (Field, Woodson, Greenberg, & Cohen, 1982;Termine & Izard, 1988).…”
Section: Discoveries From New Disciplines Utilizing New Technologiesmentioning
confidence: 99%
“…There is evidence that such automatic mimicry is innate (Field, Woodson, Greenberg, & Cohen, 1982;Termine & Izard, 1988).…”
Section: Discoveries From New Disciplines Utilizing New Technologiesmentioning
confidence: 99%
“…tongue protrusion; mouth opening) were reliably mimicked and several studies failed to replicate the results [18 -22]. In particular, few reports exist of new-born infants mimicking emotional facial expressions (but see [23]). Neonatal imitation is thus likely a specific reaction to a particular condition, which should be differentiated from general facial mimicry, and facial mimicry in reaction to emotional expressions may not be present from birth and postnatally acquired.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive developmental approach in the first half of the 20th century (1) assumed that imitation of observed actions occurs at the earliest from 10 -12 mo of age, based on learning and experience. Since the 1970s, a series of studies (2)(3)(4)(5)(6)(7)(8)(9) has confirmed that infants even as young as a few hours old can imitate proprioceptively guided behaviors. Despite these findings, neonatal imitation remained a controversial "fuzzy phenomenon" (10).…”
mentioning
confidence: 99%